ANALISIS APLIKASI QUIZIZZ SEBAGAI MEDIA EVALUASI PEMBELAJARAN DI SEKOLAH DASAR : SYSTEMATIC LITERATURE REVIEW (SLR) - Ira Rihhadatul ’Aisy Haafidzoh; Saadiyah Fajar; Aulia Nissa Arti; Fina Rahma; Nurlaila Ana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Community empowerment through productive activities is one strategy to increase individual and group independence. One such activity is hydroponic vegetable cultivation. This study aims to describe the empowerment stages implemented through hydroponic planting activities in the Kemuning Women's Farmers Group (KWT) in Cibeber Village, Cilegon City. The study used a qualitative descriptive approach, with data collection techniques including interviews and documentation. The results indicate that empowerment activities were implemented through four main stages: site selection, program socialization, implementation of empowerment activities, and member self-reliance. In the initial stage, site selection took into account accessibility, land conditions, and the availability of local resources. The socialization stage was conducted to increase members' understanding of the benefits and techniques of hydroponic cultivation. The implementation stage was realized through practical activities such as planting, maintenance, and harvesting. Meanwhile, the self-reliance stage was demonstrated through the development of members' creativity and innovation in optimizing land and planting systems. This program provides social and economic benefits for members and the surrounding environment.